URGENT !! Hi guys I really need help quickly, Can anybody please solve these and also write/type out each part of the equation that shows how u got the final answer. I will also give brainliest.

URGENT Hi guys I really need help quickly Can anybody please solve these and also writetype out each part of the equation that shows how u got the final answer class=

Respuesta :

Answer:

Question 1: 9

Question 2: -48

Question 3: 32

Question 4: 10

Step-by-step explanation:

Question 1 explanation: Since the function is f(2), that means you need to replace all variables as 2, which will be [tex]2 * 2^2 - 3 * 2 + 7 = 2 * 4 - 6 + 7 = 8 +1 =9[/tex].

Question 2 explanation: Since the function is f(-4), that means you need to replace all variables as -4, which will be [tex]-1* (-4)^2 + 8 * (-4) = -1 * 16 + -32 = -16 -32=-48[/tex].

Question 3 explanation: Since the function is f(5), that means you need to replace all variables as 5, which will be [tex]9 * 5 -13 = 45 - 13=32[/tex].

Question 4 explanation: Since the function is f(-3), that means you need to replace all variables as -3, which will be [tex]3 * (-3)^2-17 =3*9-17=27-17=10[/tex].

Answer:

1

  • f(x) = 2x² - 3x + 7
  • f(2) = 2(2²) - 3(2) + 7 = 9

2

  • f(x) = -x² + 8x
  • f(-4) = -(-4)² + 8(-4) = -48

3

  • f(x) = 9x - 13
  • f(5) = 9(5) - 13 = 32

4

  • f(x) = 3x² - 17
  • f(-3) = 3(-3)² - 17 = 10

----------------------------------

1, No

  • x + 4 can't be a factor of x³ + 2x³ - x - 2 as 4 is not a factor of 2

2, Yes

  • x + 1 is a factor of x⁴ + 2x³ + 2x² - 2x - 3, see below
  • x⁴ + 2x³ + 2x² - 2x - 3 =
  • (x⁴ + x³) + (x³ + x²) + (x² + x) - (3x + 3) =
  • x³(x + 1) + x²(x + 1) + x(x + 1) - 3(x + 1)

As we see each term has a factor of x + 1, hence confirmed